Corporeidade e dança: reflexões para o ensino - FERREIRA, Roberta Miranda (2015)
The instrumentalization of the body, one of the legacies of the Cartesian paradigm, shows concerned with the production and the income of limited physical performance techniques, grounded in human-machine model. Therefore, it is common to find evidence on the dance education in non-formal settings, with methodologies that emphasize technical perfection of movement and excellence in choreographic performance, from the reproduction of coreographies, getting away from what is meant to be corporeality sought by and for the dance. Therefore, the objective of this study was to investigate how are the practices of dance teachers of non-formal learning environments, the city of Uberaba, in order to identify whether these forms of teaching treated the body, interwoven by the paradigm of embodiment, as a possibility of awareness of the human being. Thus, this study was characterized as exploratory and descriptive qualitative approach, in wich data collection was conducted through structured interviews and, for the interpretation of the discourse of this instrument, we used the Units Preparation and Meaning Analysis Technique. The results showed that teachers consider important the teaching of dance, from the human development perspective, in line with the technical skills, way of life, expression and kinds. The meanings attributed to the body, in the dance, represented form of expression, working tool, body and mind, corporeality and body type. The teachers' conceptions about teaching dance and its interfaces with the embodiment showed that they are interested in basing their practice in meaningful learning and that its purposes are engaged in the experience of seeking the sensitivity of surrendering to move the expression techniques. Watching the practices of the subjects, according to these assumptions, enabled to understand the aspects that distance or approach an integral formation of the human being and that these values are independent of the technical accuracy of the type of dance, but from what the teacher believes as essential about what to teach from his conception of dance. As rigid as a genre is, it can be taught in line of the assumptions of the corporeity and it’s understood that the detachment of not having working technique reflects a lack of care for the dancing bodies.